2016
DOI: 10.1519/jsc.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cycling vs. Running Training on Endurance Performance in Preparation for Inline Speed Skating

Abstract: Winter weather conditions restrict regular sport-specific endurance training in inline speed skating. As a result, this study was designed to compare the effects of cycling and running training programs on inline speed skaters' endurance performance. Sixteen (8 men, 8 women) high-level athletes (mean ± SD 24 ± 8 years) were randomly assigned to 1 of 2 groups (running and cycling). Both groups trained twice a week for 8 weeks, one group on a treadmill and the other on a cycle ergometer. Training intensity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…The finding from first component also reveals that the male secondary pupils are attributable to high capacity in cardiovascular endurance (VO2 max). This result is similar to the previous study which indicated that cardiovascular endurance provides athletes with energy to carry out their sporting activities with vigor [17]. Moreover, cardiovascular endurance is a must have component for contribution in any type of sports [18].…”
Section: Resultssupporting
confidence: 91%
“…The finding from first component also reveals that the male secondary pupils are attributable to high capacity in cardiovascular endurance (VO2 max). This result is similar to the previous study which indicated that cardiovascular endurance provides athletes with energy to carry out their sporting activities with vigor [17]. Moreover, cardiovascular endurance is a must have component for contribution in any type of sports [18].…”
Section: Resultssupporting
confidence: 91%
“…First component from PCA also has revealed that the male youth are attributable to high capacity in cardiovascular endurance (VO 2 max ). This result is similar to the previous study which indicated that cardiovascular endurance provides athletes with energy to carry out their sporting activities with vigor [33]. Moreover, cardiovascular endurance is a compulsory component for contribution in any type of sports.…”
Section: Discussionsupporting
confidence: 92%
“…At the end of the 300-m time trial, peak HR and [La -] values did not differ among categories and were similar to previous values of in-line speed skaters. 23 In particular, as cycling exercise have physiological responses comparable to running and in-line skating, 23 the results of [La -] are in line with studies reporting no differences between adolescents and adults in response to a maximum Wingate anaerobic test. 24 Accordingly, RPE values displayed a very high level of effort exerted by the skaters of all groups, which is also supported by the similar SJdelta among groups.…”
Section: Skating Performance and Physiological Responsessupporting
confidence: 67%